Bilious emesis as presenting symptom of congenital diaphragmatic hernia in an 8-month-old - Daphney Clermont; Janice A. Taylor (Elsevier, 2017)
Although congenital diaphragmatic hernia (CDH) primarily presents in either the prenatal or neonatal period, late presentation has a reported incidence of 2.5-25%. This case report describes an 8-month-old-male who presented to the emergency department with dehydration and a 24-h history of bilious emesis. Work-up led to the diagnosis of a left-sided Bochdalek CDH. He subsequently underwent laparoscopic diaphragmatic hernia repair with reduction of near-total length of incarcerated bowel. The patient had an uneventful recovery. Babies born with CDH are typically unstable at birth, and even with repair, the mortality rate remains high. However, in the case of delayed CDH diagnosis where there are no perinatal issues, surgical repair has very high success rates, provided that there are no complications regarding the delay. If there is not a high index of suspicion based on the patient's history and exam, delayed diagnosis and intervention with late CDH presentations can lead to complications which could otherwise be minimized. The purpose of this case report is to raise awareness and contribute to the growing knowledge about delayed CDH presentation among physicians and surgeons to facilitate early diagnosis and care of a morbid yet manageable condition.